Virtual Reality Therapeutic Art for Adult Hospitalized Patients and Caregivers: A Mixed-Methods Project - Sophina McDaniel; Rachyl Pines; Emily M. He; Faith Collins; Faaizah Arshad; Maria Menendez; Vishnunarayan Girishan Prabhu; Thomas J. Caruso (Journal of Patient Experience)
Increased stress, anxiety, and depression hinder recovery of hospitalized patients. Mindfulness therapies, which adopt a holistic approach to patient care, reduce anxiety, and depression. This quality improvement initiative evaluated the implementation of a virtual reality (VR) therapeutic art program at Stanford Health Care from February to June 2024, providing an innovative and scalable adjunct to traditional art and music mindfulness therapies. This mixed methods project piloted 84 cumulative hours with 105 participants. Outcomes investigated satisfaction and the impact on hospitalization experience via survey questions. Data were analyzed using descriptive statistics and thematic analysis. Results (n = 40) indicated substantial improvements in patient experience, with 85% recommending the program and 97.5% reporting positive impacts from VR engagement. Thematic analysis of open-ended survey responses identified 4 key themes: escape and distraction, therapeutic benefits, enjoyment of the interactive activity, and positive facilitator interactions. Participants also expressed interest in additional VR offerings, including virtual mindfulness, and meditation. The results suggest that VR can serve as an effective adjunct to conventional mindfulness therapies and improve the inpatient experience.